Penggunaan Campur Kode Guru dalam Pembelajaran Bahasa Jepang Kelas XI IBB di SMAS LAB UNDIKSHA - Alit Mandala, Ayu Kris Utari Dewi; Dwipayanti, Ni Kadek; Tiara Karunia Dewi, Putu; Dewi Merlyna, Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 5 No 2 (2023), 2023)
The purpose of the study is to examine how Japanese language instructors used mixed codes in Japanese class XI IBB at the Undiksha Laboratory Private High School. Non-participation observation techniques were used in this study as qualitative descriptive methodologies. This study focused on a Japanese instructor at SMAS Laboratory Undiksha Class XI Language. The utterances made by Japanese teachers while engaging students in learning activities served as the study's data source. According to the findings of this investigation, Japanese professors at SMA Private Laboratory Undiksha sometimes mix codes externally. The research findings are presented in the form of a conversation between the teacher and the students, followed by a descriptive technique.